Legal Protection for Women Victims of Revenge Porn Crimes Who Experience Victimblaming - Kalia, Thifana Dewi; Kayowuan L, Kayus (Universitas Islam Sultan Agung, 2023)
The concept of victim blaming is the justification of injustice by finding defects or faults in victims, in the concept of victim blaming women as victims who are blamed through words and sentences in media reports, women at one time are described as victims as well as triggers for rape that befalls them. In the case of revenge porn cyber-based sexual violence, the victim experiences losses that threaten mentally/psychologically as a result of the victimblaming that has been experienced by the victim, of course, the form of compensation in the form of material or money is inadequate if it is not accompanied by efforts to recover the victim's mentality. The type of research used by the author is normative juridical research, which is research that refers to research involving laws and regulations, court decisions, and legal practices in society. By using a statutory approach, a case approach. There is no specific law governing revenge pornography, but there are laws that can be alternatives to protect victims, such as: 1. Law Number 31 of 2014 concerning the Protection of Witnesses and Victims, 2. Law Number 39 of 1999 concerning Human Rights, 3. Law Number 1 of 1946, 4. Law Number 19 of 2016 concerning Electronic Information and Transactions, 5. Law Number 44 of 2008 concerning Pornography, 6. Law Number 12 of 2022 concerning Sexual Violence